Species-specific pulmonary arterial asymmetry determines species differences in regional pulmonary perfusion. - Burrowes, K; Hoffman, E; Tawhai, M (2009)
The functional significance of differences in pulmonary vascular branching and diameter asymmetry between the human and quadruped lung has not previously been addressed. To evaluate the contribution of branching asymmetry to observable species differences in blood flow gradients, computed distributions of blood flow were compared in structure-based models of the human and ovine pulmonary arteries. The models were derived using a combination of computed tomography and a volume-filling algorithm. Pressure, flow, and deformed vessel diameter were calculated in both species models using equations representing conservation of mass and momentum, and a pressure-diameter relationship. The major difference between the human and ovine results was the presence of a large region of "zone 4" flow and higher mean flows in the central region of the ovine lung compared to that in the human. Heterogeneity in tissue perfusion and the contribution of gravity were similar in both species models; however, the gravitationally directed gradients of perfusion in the human and ovine models were different and each consistent with human and quadruped measurements, respectively. The results suggest that measured species differences in pulmonary perfusion gradients are largely determined by differences in branching asymmetry.